Predictors of health-related quality of life among older adults living with HIV in Thailand: results from the baseline and follow-up surveys - Patou Masika Musumari (2020)
© 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group. The current longitudinal study consisted of baseline and follow-up surveys among older adults living with HIV (OALHIV) in Thailand. The health-related quality of life (HRQoL) was assessed using the Medical Outcomes Study HIV (MOS-HIV) questionnaire. We performed multiple linear regression analysis to document correlates of HRQoL at baseline and the predictors of the changes in HRQoL at follow-up. Of the 364 participants recruited at baseline; 327 (89.9%) completed the follow-up survey. The mean (SD) Physical Health Summary (PHS) and Mental Health Summary (MHS) scores were respectively 49.8 (7.3) and 53.2 (6.4). There was a significant increase in the mean score of most of the MOS-HIV domains, ranging between 1.3 for the PHS and 26.9 for the energy/fatigue dimension. In contrast, the mean score significantly decreased by 4.1 and 10.3 points, respectively for the cognitive and social functioning. Female gender was a predictor of the decline in social (β =−11.37; P = 0.031) and cognitive (β =−8.05; P = 0.002) functioning at follow-up, while being married was related to an increase of in the score of energy/fatigue (vitality) (β = 5.98; P = 0.011) at follow-up. Physical exercise was associated with an increase in social functioning (β = 9.38; p = 0.042). Overall the HRQoL of OALHIV improved or was maintained over time.